Impact of agricultural management practices on soil organic carbon: simulation of Australian wheat systems. (26th February 2013) - Zhao, Gang; Bryan, Brett A.; King, Darran; Luo, Zhongkui; Wang, Enli; Song, Xiaodong; Yu, Qiang
Abstract Quantifying soil organic carbon (SOC) dynamics at a high spatial and temporal resolution in response to different agricultural management practices and environmental conditions can help identify practices that both sequester carbon in the soil and sustain agricultural productivity. Using an agricultural systems model (the Agricultural Production Systems sIMulator), we conducted a high spatial resolution and long‐term (122 years) simulation study to identify the key management practices and environmental variables influencing SOC dynamics in a continuous wheat cropping system in Australia's 96 million ha cereal‐growing regions. Agricultural practices included five nitrogen application rates (0–200 kg N ha−1 in 50 kg N ha−1 increments), five residue removal rates (0–100% in 25% increments), and five residue incorporation rates (0–100% in 25% increments). We found that the change in SOC during the 122‐year simulation was influenced by the management practices of residue removal (linearly negative) and fertilization (nonlinearly positive) – and the environmental variables of initial SOC content (linearly negative) and temperature (nonlinearly negative). The effects of fertilization were strongest at rates up to 50 kg N ha−1, and the effects of temperature were strongest where mean annual temperatures exceeded 19 °C. Reducing residue removal and increasing fertilization increased SOC in most areas except Queensland where high rates of SOC decomposition caused by high temperature and soil moisture negated these benefits. Management practices were particularly effective in increasing SOC in south‐west Western Australia – an area with low initial SOC. The results can help target agricultural management practices for increasing SOC in the context of local environmental conditions, enabling farmers to contribute to climate change mitigation and sustaining agricultural production.